2022
DOI: 10.2196/30456
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Simulation Training for Cardiopulmonary Resuscitation After Cardiac Surgery: Face and Content Validity Study

Abstract: Background Cardiac arrest after cardiac surgery commonly has a reversible cause, where emergency resternotomy is often required for treatment, as recommended by international guidelines. We have developed a virtual reality (VR) simulation for training of cardiopulmonary resuscitation (CPR) and emergency resternotomy procedures after cardiac surgery, the Cardiopulmonary Resuscitation Virtual Reality Simulator (CPVR-sim). Two fictive clinical scenarios were used: one case of pulseless electrical acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Most enjoyed the CPVR-sim (86%), and using VR simulations for learning purposes (86%) The software was easy to use (72%) and quick to learn (93%), without needing written instructions (79%) Rodríguez-Matesanz et al [ 19 ] 2022 Madrid, Spain To highlight the limitations of traditional methods using mechanical manikins and the benefits of the new approaches that involve the students in virtual, immersive, and dynamic environments Cross-sectional study Basic CPR ND ND Convenience sampling 33 participants: 15 HCPs, 10 medical students, 6 professors and 2 traditional objective structured clinical exam examiners, from different nationalities 45.5% participants never tested a VR application before Age: 19 to 57 years Female: ND Hospital CPR-OSCE VR is a software application that can be executed both on PC or with Oculus Quest It featured multiple scripts to visualize the different environment props and characters, track the user’s location, movement and interaction, and measure the accuracy of the CPR performance The system can be used both with and without an external physical manikin and the extra tracking devices but in this study they were used Performance metrics are generated during the simulation. The user is assisted by an external manikin that provides a point of reference in the simulation, as well as tactile feedback Not performed All participants played the same scenario Sensors for automatic detection of participant performance After the simulation a questionnaire was administrated, and regarded: (1) personal data; (2) previous experience with VR, similar technologies, and objective structured clinical exam; (3) user experience with CPR-OSCE VR; and (4) fidelity of CPR-OSCE VR 88% of the participants obtained a correct compression rate, and 65% a positive outcome in the appropriated compression depth applied to the manikin A good level of realism was present for 97% of the participants Sadeghi et al [ 28 ] 2022 Netherlands To assess the feasibility and to establish the face and content validity of two clinical scenarios (shockable and not shockable CA) of the CPVR-sim Cross-sectional study Advanced CPR ND ND Convenience sampling 41 participants: 14 cardiothoracic surgeons, 5 residents, 12 junior physicians, 6 nurse practitioners, 4 medical students. 27% had no experience with emergency resternotomy, 32% had no experience with VR and 17% had no experience with simulation training Age: 43 (IQR 38–55.5) for expert and 30 (IQR 30–42.5) for novice group Female: 14 (34%) Cardiothoracic Surgery Department The simulation was designed by a multidisciplinary team from different countries An Oculus Quest 2 head-mounted display was used, in combination with two VR controllers and a high-performance laptop Before the simulation, each participant was given a short briefing on the scenario, the use of the VR, and how to interact with the controls and software The team...…”
Section: Resultsmentioning
confidence: 99%
“…Most enjoyed the CPVR-sim (86%), and using VR simulations for learning purposes (86%) The software was easy to use (72%) and quick to learn (93%), without needing written instructions (79%) Rodríguez-Matesanz et al [ 19 ] 2022 Madrid, Spain To highlight the limitations of traditional methods using mechanical manikins and the benefits of the new approaches that involve the students in virtual, immersive, and dynamic environments Cross-sectional study Basic CPR ND ND Convenience sampling 33 participants: 15 HCPs, 10 medical students, 6 professors and 2 traditional objective structured clinical exam examiners, from different nationalities 45.5% participants never tested a VR application before Age: 19 to 57 years Female: ND Hospital CPR-OSCE VR is a software application that can be executed both on PC or with Oculus Quest It featured multiple scripts to visualize the different environment props and characters, track the user’s location, movement and interaction, and measure the accuracy of the CPR performance The system can be used both with and without an external physical manikin and the extra tracking devices but in this study they were used Performance metrics are generated during the simulation. The user is assisted by an external manikin that provides a point of reference in the simulation, as well as tactile feedback Not performed All participants played the same scenario Sensors for automatic detection of participant performance After the simulation a questionnaire was administrated, and regarded: (1) personal data; (2) previous experience with VR, similar technologies, and objective structured clinical exam; (3) user experience with CPR-OSCE VR; and (4) fidelity of CPR-OSCE VR 88% of the participants obtained a correct compression rate, and 65% a positive outcome in the appropriated compression depth applied to the manikin A good level of realism was present for 97% of the participants Sadeghi et al [ 28 ] 2022 Netherlands To assess the feasibility and to establish the face and content validity of two clinical scenarios (shockable and not shockable CA) of the CPVR-sim Cross-sectional study Advanced CPR ND ND Convenience sampling 41 participants: 14 cardiothoracic surgeons, 5 residents, 12 junior physicians, 6 nurse practitioners, 4 medical students. 27% had no experience with emergency resternotomy, 32% had no experience with VR and 17% had no experience with simulation training Age: 43 (IQR 38–55.5) for expert and 30 (IQR 30–42.5) for novice group Female: 14 (34%) Cardiothoracic Surgery Department The simulation was designed by a multidisciplinary team from different countries An Oculus Quest 2 head-mounted display was used, in combination with two VR controllers and a high-performance laptop Before the simulation, each participant was given a short briefing on the scenario, the use of the VR, and how to interact with the controls and software The team...…”
Section: Resultsmentioning
confidence: 99%
“…After the training, the trainees were asked to indicate their agreement with a series of survey items on a 5-point Likert scale (1=fully disagree, 2=disagree, 3=neutral, 4=agree, 5=fully agree) [ 22 ]. The research measures and questions are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…A virtual reality (VR) simulation (cardiopulmonary virtual reality simulator, CPVR-sim) was developed previously by our group to train physicians and members of the multidisciplinary team for several post-cardiac surgery CPR scenarios [ 6 ]. In this simulation, the user can practice scenarios repeatedly and learn the steps described within the protocol in a realistic, 360 degree, immersive, 3D environment without the need for other equipment (aside from a VR headset and controllers) or instructor-led training sessions.…”
Section: Introductionmentioning
confidence: 99%
“…In this simulation, the user can practice scenarios repeatedly and learn the steps described within the protocol in a realistic, 360 degree, immersive, 3D environment without the need for other equipment (aside from a VR headset and controllers) or instructor-led training sessions. At present, this simulator’s face and content validity have been demonstrated in a feasibility study, in which experts and their junior colleagues alike found this training method useful, easy to use, and suitable as an adjunct to conventional CPR training [ 6 ]. Such gamified learning can be used in ALS training for applications such as self-study before an ALS course, in a blended learning approach, and for learning without being dependent on the time and location of an instructor and materials [ 5 ].…”
Section: Introductionmentioning
confidence: 99%